Histone Deacetylase 1/2 Mediates Proliferation of Renal Interstitial Fibroblasts and Expression of Cell Cycle Proteins - Pang, Maoyin (J Cell Biochem, 2011)
We recently reported that the histone deacetylase (HDAC) activity is required for activation of renal interstitial fibroblasts. In this study, we further examined the role of HDACs, in particular, HDAC1 and HDAC2, in proliferation of cultured rat renal interstitial fibroblasts (NRK-49F) and expression of cell cycle proteins. Inhibition of HDAC activity with trichostatin A (TSA), blocked cell proliferation, decreased expression of cyclin D1, a positive cell cycle regulator, and increased expression of p27 and p57, two negative cell cycle regulators. Silencing either HDAC1 or HDAC2 with siRNA also significantly inhibited cell proliferation, decreased expression of cyclin D1, and increased expression of p57. However, down-regulation of HDAC2, but not HDAC1 resulted in increased expression of p27. Furthermore, HDAC1 and HDAC2 downregulaton was associated with dephosphorylation and hyperacetylation of STAT3 (signal transducer and activator of transcription 3). Blockade of STAT3 with S3I-201 or siRNA decreased renal fibroblast proliferation. Finally, mouse embryonic fibroblasts (MEFs) lacking STAT3 reduced the inhibitory effect of TSA on cell proliferation, add-back of wild type STAT3 to STAT3(−/−) MEFs restored the effect of TSA. Collectively, our results reveal an important role of HDAC1 and HDAC2 in regulating proliferation of renal interstitial fibroblasts, expression of cell cycle proteins and activation of STAT3. Further, STAT3 mediates the proliferative action of HDACs.